PERANAN KETEPATAN WAKTU (TIMELINESS) KETERSEDIAAN LAPORAN KEUANGAN YANG BERKUALITAS SUATU PERUSAHAAN TERHADAP PENGAMBILAN KEPUTUSAN - Hendri Kartika Andri; Susanto Wibowo; Novelia Kiki Permatasari; Edi Triwibowo; Ananda Septianingrum Suparyana (Universitas Tangerang Raya, 2021)
Financial Statements are products produced by the Finance Accounting & Tax (FAT) section of a company. Timeliness and accuracy of quality financial reports are very important to be presented in a decision that will be taken by the Board of Directors (BOD) and other stakeholders. The purpose of this study was to determine the role of the timeliness of a company's quality financial statements on decision making. The findings show that the speed of availability of quality financial reports is indeed very helpful and important for BOD in making direct decisions for what steps will be taken by BOD for the advancement of company performance and financial performances in the future.